2018
DOI: 10.1186/s13013-018-0157-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of posterior spinal fusion for the correction of adolescent idiopathic scoliosis

Abstract: BackgroundAdolescent idiopathic scoliosis (AIS) is the most common form of idiopathic scoliosis, and surgery is considered as one of the therapeutic options. However, it is associated with a variety of irreversible complications, in spite of the benefits it provides. Here, we evaluated the long-term outcome of posterior spinal fusion (PSF) of AIS to shed more light on the consequences of this surgery.MethodsIn a cross-sectional study, a total of 42 AIS patients who underwent PSF surgery were radiographically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Although there are no reported differences in blood loss, length of hospital stay and patient reported outcomes between both approaches, the posterior approach may save on the negative impacts of the anterior approach on pulmonary function. Studies also showed that the posterior-only approach has the same correction as a combined anterior/posterior spinal fusion, without the need for entering the thorax and thus negatively impacting pulmonary function [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71].…”
Section: Surgical Managementmentioning
confidence: 99%
“…Although there are no reported differences in blood loss, length of hospital stay and patient reported outcomes between both approaches, the posterior approach may save on the negative impacts of the anterior approach on pulmonary function. Studies also showed that the posterior-only approach has the same correction as a combined anterior/posterior spinal fusion, without the need for entering the thorax and thus negatively impacting pulmonary function [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71].…”
Section: Surgical Managementmentioning
confidence: 99%
“…A cross-sectional study evaluated clinical outcomes via the Oswestry Disability Index (ODI) and VAS score in AIS patients who underwent posterior spinal fusion (PSF) surgery and followed for a mean 5.6 years. 92 DD was observed in 16% of patients, but it was not associated with preoperative or postoperative vertebral tilt, VAS and ODI scores. Other residual deformities and their relationship to pain have been explored by various studies.…”
Section: Fusion Surgerymentioning
confidence: 84%
“…12 Although the percentage of patients who develop ASD following PSF varies among studies, one study that specifically addressed adolescents found that 16% of patients who had normal discs on initial preoperative imaging developed ASD. 13 Most cases of ASD develop within the first 3-5 years following initial PSF. 13 Studies have shown that anywhere from 2.6-27.4% of adult patients who have been treated with lumbar PSF undergo additional surgery for ASD that did not respond to conservative treatment.…”
Section: Adjacent Segment Disease (Asd)mentioning
confidence: 99%
“…13 Most cases of ASD develop within the first 3-5 years following initial PSF. 13 Studies have shown that anywhere from 2.6-27.4% of adult patients who have been treated with lumbar PSF undergo additional surgery for ASD that did not respond to conservative treatment. 12 This number is likely lower in the short term among AIS patients who tend to be younger and, therefore, have less degeneration; however, in the long term, it may prove higher as the fusion constructs are longer and the patients have more years of life ahead of them to develop degeneration.…”
Section: Adjacent Segment Disease (Asd)mentioning
confidence: 99%